Activity manifestation of the media auditoriums in the multimedia environment - Siudikienė, Daiva (Information & Media, 2015)
The purpose of this article is to present the research of the Lithuanian media users which revealed that audience activity and selectivity gain new shapes in the multimedia environment. Processes of media digitisation and convergence generate new practices for the use of media and models of activity and the selectivity of audiences. Audience participants have the opportunity to make their selections from various platforms and an array of content, although little is known about the ways in which individuals perform their selections in a multimedia environment, which has a totally distinct nature and operational logics than that of traditional media. The growing activity of the audience is one of the most important problems in the study of audience that may be associated with the corresponding characteristics of audiences. This encourages a more profound investigation of the peculiarities of a contemporary audience activity and the factors that determine them. An abundance of descriptions of contemporary media audience participants attest to the fact that their operation in the multimedia environment is much more active and variable than in the previous stages of media development. If in the era of traditional mass communication, activity was primarily understood as selection performed by media users of what and when should be used, nowadays this activity has obtained new shapes. Moreover, a media user may well act as a creator, distributor, and consumer of the media content, while the content that is generated by the media users becomes dominant in the electronic space. It has been stated that media users select media and their content, and compose them into a unified structure, in relation with a coherent behaviour strategy which reflects the activity and selectivity of an individual and his/her loyalty to particular media and their content. Media users form their media repertoires, selecting a definite number of channels and range of dominant content, align their use to a daily routine and combine with other activities.